1992
DOI: 10.1063/1.463955
|View full text |Cite
|
Sign up to set email alerts
|

Direct energy transfer from excited organic adsorbates to intrinsic defect sites in silicalite

Abstract: The decay of the excited singlet state of an aromatic molecule such as naphthalene adsorbed to the surface of silica is nonexponential. This nonexponential decay is shown to result from a multipolar interaction between the excited adsorbate and the intrinsic defects of silica. We present experimental evidence for direct energy transfer between the donor molecules, naphthalene and 2-methoxynaphthalene, and acceptor defects sites of a crystalline silica zeloite (silicalite). The principal condition for direct en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The high concentration of the defect sites with two adjacent silanol groups (disilanols) was also demonstrated in Na and proton exchange and in NMR experiments on TPA-templated zeolite ZSM-5 . A direct energy transfer from the excited adsorbates to the structural defects was reported in optical experiments on silicalites (thermal deflection spectroscopy), which allowed the authors to estimate the defect concentration as one defect per unit cell; the optical absorption of the defect sites was thus identified at 293 and 283 nm, which in comparison with previously reported data suggested that the defect sites are either peroxy bridges or peroxy radicals. The role of dioxygen species formed at or next to Brønsted sites was also discussed in the context of Lewis and redox activity of zeolites based on the EPR data .…”
supporting
confidence: 56%
“…The high concentration of the defect sites with two adjacent silanol groups (disilanols) was also demonstrated in Na and proton exchange and in NMR experiments on TPA-templated zeolite ZSM-5 . A direct energy transfer from the excited adsorbates to the structural defects was reported in optical experiments on silicalites (thermal deflection spectroscopy), which allowed the authors to estimate the defect concentration as one defect per unit cell; the optical absorption of the defect sites was thus identified at 293 and 283 nm, which in comparison with previously reported data suggested that the defect sites are either peroxy bridges or peroxy radicals. The role of dioxygen species formed at or next to Brønsted sites was also discussed in the context of Lewis and redox activity of zeolites based on the EPR data .…”
supporting
confidence: 56%
“…[66] A direct energy transfer from the excited adsorbates to the structural defects was reported in optical experiments on silicalites (thermal deflection spectroscopy). [81] The authors estimated the defect concentration at one species per unit cell. The optical absorption of the defect sites was identified at 293 nm and 283 nm, which by comparison with previously reported data suggested that the defect sites are either peroxy bridges or peroxy radicals.…”
mentioning
confidence: 99%
“…A general finding is that the kinetics of the reactions are more complex than those in bulk solvent. This is not unexpected due to the heterogeneous nature of the surfaces, and possibly due to fractal effects. 2jk, For the most part, the observed chemistry can be described by reasonable models involving expected properties of the oxide surfaces. The photochemistry in these systems occurred at solid−vacuum or solid−gas interfaces.…”
Section: Introductionmentioning
confidence: 70%
“…Photoinduced reactions of molecules on silica and alumina surfaces 2fg,3 have been the focus of numerous studies. A general finding is that the kinetics of the reactions are more complex than those in bulk solvent.…”
Section: Introductionmentioning
confidence: 99%